Group 2 innate lymphoid cells in nasal polyposis - Stevens, Whitney W. (Ann Allergy Asthma Immunol, 2020)
OBJECTIVE: Chronic rhinosinusitis with nasal polyps (CRSwNP) is characterized by a chronic type 2 inflammatory response in the paranasal sinuses. Group 2 innate lymphoid cells (ILC2) are potent innate immune cells that contribute to type 2 inflammation by producing cytokines such as IL-4, IL-5 and IL-13. There is increasing evidence suggesting that ILC2 play an important role in CRSwNP pathogenesis. DATA SOURCES: We reviewed published literature obtained through PubMed inquiries. Study Selections: Studies relevant to the presence, function, and activation of ILC2 in CRSwNP were included. RESULTS: Nasal polyps (NP) are one of the first tissues in which human ILC2 were discovered and many groups have since reported these cells are significantly elevated in NP. ILC2 in NP are also highly activated and produce type 2 cytokines in vivo . Mediators known to activate ILC2 including RANK-L, TSLP, various lipid mediators (including prostaglandin D 2 and cysteinyl leukotrienes), IL-4, and IL-13 have also been shown to be elevated in NP compared to healthy sinonasal tissue. Other well- known ILC2 activators, IL-25 and IL-33 are sometimes elevated in NP in some countries. Furthermore, activation of ILC2 via four distinct transcriptional pathways (NF-kB, NFAT, STAT5 and STAT6) is needed for the most robust generation of type 2 cytokines. CONCLUSION: ILC2-mediated type 2 inflammation plays a crucial role in the pathogenesis of CRSwNP. Targeting upstream mediators responsible for activating ILC2 as well as downstream products these cells release may play an important role in modifying the inflammatory response and improving clinical outcomes in CRSwNP.